Tinjauan Yuridis Terhadap Penghapusan KPK Serta Pelimpahan Hak, Kewajiban, dan Wewenang Aparatur Hukum - Abdallah, Raffi Ikzaaz; Bintang A, Immanuel Given; Nadjima, Aulia Rachmatullah; Putra, Alfarel Endito; Tamir A, Sulthan Muhammad; Prasetyo, Handoyo (Penerbit Yayasan Daarul Huda Kruengmane, 2024)
The Corruption Eradication Commission (KPK) was founded in 2003 as a response to widespread corruption in Indonesia. The Corruption Eradication Committee has the authority to carry out investigations, prosecutions and prevent corruption. The KPK has succeeded in arresting and imprisoning many big-time corruptors, including high-ranking state officials. However, in recent years, the KPK has been faced with various challenges. One of the biggest challenges is the revision of the KPK Law (UU) which is considered to weaken the authority of the KPK. Apart from that, the Corruption Eradication Commission was also criticized because it was considered not transparent and accountable. In this article the author tries to look at the juridical review of the issue of eliminating the Corruption Eradication Commission. From the data obtained, it was found that First, the legal basis for disbanding the KPK must be considered carefully, considering the important role of this institution in eradicating corruption in Indonesia. The legal implications of disbanding the KPK are very important for the law enforcement system in Indonesia. This deletion could create gaps in the mechanisms for monitoring and prosecuting corruption cases and reduce public confidence in the Government's commitment to eradicating corruption. Third, the transfer of the rights, obligations and authority of the Corruption Eradication Committee to other legal entities must be carried out according to clear and transparent procedures.